Pengaruh Inokulasi Trichoderma sp. Indigenus terhadap Penyakit Akar Gada dan Pertumbuhan Tanaman Kubis (Brassica oleracea L.) - ANTARI, NI PUTU MERRY SENI; PUSPAWATI, NI MADE; SUADA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.4, Oktober 2017, 2017)
The Influence of Indigenous Trichoderma sp. Inoculation against Clubroot and the Growth of Cabbages (Brassica oleracea L.) The Cabbage (Brassica oleracea L.) is a plant that contains many vitamins and minerals needed by human. The problem which often experienced by cabbage farmers is clubroot deseases that caused by pathogenic Plasmodiophora brassicae Worr. Eco-friendly controls are needed so as not to adversely affect ecosystems by using natural enemies of the pathogen such as Trichoderma sp. The purpose of this research was to obtain the type Trichoderma sp. which effectively suppress clubroot and increase the growth of cabbage plants. The results showed that the most effective isolate was isolate from zucchini plant (Cucurbita pepo L.) rhizosphere (T1), followed by tomato plant (Lycopersicon esculentum L.) rhizosphere (T2), romana plant (Lactuca sativa L. var. longifolia) rhizosphere (T4), and from the spinach plant (Spinacia oleracea L.) rhizosphere (T9). The isolates were able to decrease clubroot and promote cabbage plant growth as well.